Challenges Faced by Women Offenders After Incarceration - Ng, Vanessa (Women & criminal justice, 2021)
The growing body of gender-responsive research on women offenders revealed fundamental differences between women and men offenders. However, limited research studies are available about the challenges of women offenders in Singapore. This qualitative study seeks to explore: (1) What are the post-incarceration challenges Singapore women offenders face; and (2) How do the post-incarceration challenges differ for women re-offenders versus desistors? Singapore women offenders faced challenges in the following 9 broad domains of (1) employment; (2) financial; (3) social network; (4) mental health; (5) role as a mother; (6) housing; (7) role as a caregiver; (8) leisure time; and (9) individual factors. Re-offenders tend to report more complex challenges, especially in the domains of social network and role as a mother. These findings highlight that reintegration is a gendered and context-dependent process that is shaped by women’s experiences.